A Re-Examination of the History of Etiologic Confusion between Dengue and Chikungunya. - Goro Kuno (Public Library of Science (PLoS), 2015)
Contrary to the perception of many researchers that the recent invasion of chikungunya (CHIK) in the Western Hemisphere marked the first episode in history, a recent publication reminded them that CHIK had prevailed in the West Indies and southern regions of the United States from 1827-1828 under the guise of "dengue" (DEN), and that many old outbreaks of so-called "dengue" actually represented the CHIK cases erroneously identified as "dengue." In hindsight, this confusion was unavoidable, given that the syndromes of the two diseases-transmitted by the same mosquito vector in urban areas-are very similar, and that specific laboratory-based diagnostic techniques for these diseases did not exist prior to 1940. While past reviewers reclassified problematic "dengue" outbreaks as CHIK, primarily based on manifestation of arthralgia as a marker of CHIK, they neither identified the root cause of the alleged misdiagnosis nor did they elaborate on the negative consequences derived from it. This article presents a reconstructed history of the genesis of the clinical definition of dengue by emphasizing problems with the definition, subsequent confusion with CHIK, and the ways in which physicians dealt with the variation in dengue-like ("dengue") syndromes. Then, the article identifies in those records several factors complicating reclassification, based on current practice and standards. These factors include terms used for characterizing joint problems, style of documenting outbreak data, frequency of manifestation of arthralgia, possible involvement of more than one agent, and occurrence of the principal vector. The analysis of those factors reveals that while some of the old "dengue" outbreaks, including the 1827-1828 outbreaks in the Americas, are compatible with CHIK, similar reclassification of other "dengue" outbreaks to CHIK is difficult because of a combination of the absence of pathognomonic syndrome in these diseases and conflicting background information.